Thromboembolism and Pregnancy - Ginsberg, Jeffrey S. (Thrombosis and Haemostasis, 1999)
Antithrombotic therapy during pregnancy is used for the treatment and prophylaxis of venous thromboembolic disease, for the prevention and treatment of arterial embolism associated with valvular heart disease and/or prosthetic heart valves, for the prevention of fetal growth retardation and pregnancy loss in patients with antiphospholipid antibodies, and in patients with pregnancy-induced hypertension. Since antithrombotic agents have the potential to produce complications in both the mother and fetus, their use during pregnancy raises concerns. Guidelines are difficult to establish because the evidence upon which recommendations are based is derived primarily from poor-quality studies. This chapter reviews the fetal and maternal effects of antithrombotic agents including oral anticoagulants, unfractionated heparin, low molecular weight heparins (LMWH), and aspirin, and provides recommendations for their use during pregnancy.